Facile green synthesis of lanthanum oxide nanoparticles: their photocatalytic and electrochemical applications - C, Mallikarjunaswamy; L, Soundarya T.; Al-Kahtani, Abdullah A.; Al-Odayni, Abdel-Basit; G, Nagaraju; Ranganatha, Lakshmi (Journal of materials science. Materials in electronics, 2024)
Green synthesis is a reliable way to synthesize metal oxide nanoparticles (NPs) without affecting the environment. Plant extracts act as reducing agents that favor the synthesis of NPs. In this study, jackfruit aqueous extract was used as a fuel in the solution combustion synthesis of lanthanum oxide (La 2 O 3 ) NPs. X-ray diffraction (XRD) confirmed the formation of the hexagonal structure of La 2 O 3 NPs. The scanning electron microscope (SEM) and energy dispersive X-ray (EDS) spectrum confirm the needle-shaped morphology and purity of the La 2 O 3 NPs, respectively. Furthermore, La 2 O 3 was utilized as a photocatalyst for the photodegradation of methylene blue dye under visible light radiation, demonstrating high efficiency within 90 min of light irradiation. The electrochemical characteristics of La 2 O 3 were studied using a carbon paste electrode in a 0.1 M HCl solution. These La 2 O 3 samples exhibited superior sensitivity in cyclic voltammetry tests towards the detection of ascorbic acid and lead nitrate. Consequently, La 2 O 3 holds potential for applications in electrochemical sensor technology.